Elevated serum uric acid is associated with cognitive improvement in older American adults: A large, population-based-analysis of the NHANES database - Geng, Rulin; Zhang, Yu; Liu, Miao; Deng, Shengfeng; Ding, Jingwen; Zhong, Hongfei; Tu, Qiuyun (Frontiers in Aging Neuroscience, 2022)
Background The many studies revealing a connection between serum uric acid (SUA) and dementia have reported conflicting results. This study sought to investigate the relations between SUA and cognitive function in older adults. Materials and methods The sample was 2,767 American adults aged ≥60 years from the National Health and Nutrition Examination Survey 2011–2014. Cognitive performance was evaluated by the Consortium to Establish a Registry for Alzheimer’s Disease test, animal fluency test, digit symbol substitution test, and composite z-score. Multivariate linear regression analyses were conducted to estimate the association between SUA and cognitive function. Results SUA level and cognitive function were significantly, positively correlated. Age significantly correlated with the association between SUA and cognitive function. Conclusion These findings support a connection between SUA and cognition, showing a positive link between SUA and cognitive scores among older American adults. We contend that a slight rise in uric acid within the normal range is advantageous for enhanced cognition. To confirm the precise dose-time-response relation, more tests will be needed.